Ethanolic Extract of Papaya (Carica papaya) Leaf Exhibits Estrogenic Effects In Vivo and In Silico - Sugiyanto, Raisatun Nisa; Khamsita, Rahmi; Lambertus, Marvin; Utomo, Rohmad Yudi; Susidarti, Ratna Asmah (Indonesian Research Gateway, 2012)
The menopause women have the low level of estrogen in the body. The lack of estrogen changes physiological function in womens body that affects in health condition. Carica papaya L. leaf contains flavonoid quercetin which exhibits estrogenic effect. The aim of this study is to determine the estrogenic effect of papaya leaves extract (PLE) in vivo, and in silico. Papaya leaves were extracted by ethanol 70% maceration. The in silico study were done by molecular docking between quersetin and Estrogen Receptor (ERÎ± and ERÃ) to obtain the docking score. Based on this study, docking score of quercetin was almost similar to the native ligand of ER. The in vivo study was done as follow: 36 female rats Sprague Dawley divided into six groups. The groups are shame-ovariectomized (S-OVX), control ovariextomized (OVX), CMC-Na control (OVX+CMC-Na), positive control (OVX+Estradiol), and the PLE treatment groups dose 750 mg/kgBW (OVX+750mg/kgBW) and dose 1000 mg/kgBW (OVX+1000 mg/kgBW). Administrations of PLE were done in three weeks orally, while estradiol was administrated intraperitonially. The mammae and uterine were sliced for analysis. Based on the study, the treatment of PLE increased the number of mammae lobules and uterine weight as well as estrogen does. In summary, PLE can be developed as a source of phytoestrogens.Keywords: Carica papaya L., phytoestrogen, estrogen receptor, mammae lobule, uterine